The Impact of Corporate Governance and Investment Opportunity Set on Financial Performance - Sri Maryati; Tiara Anggraini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to empirically examine the effect of the board of commissioners, board of directors, audit committee, and investment opportunity set on financial performance. This study uses a quantitative method with secondary data, namely the financial statements of manufacturing companies listed on the IDX for 2019-2021. The data in this study were processed using SPSS 25. The results showed that the board of commissioners, board of directors, and audit committee had no effect on financial performance, but the investment opportunity set had a significant positive effect on financial performance. Based on the results of the study it can be concluded that Investment Opportunity Set affects the ups and downs of the financial performance of manufacturing companies and Good Corporate Governance does not affect the company's financial performance.